The Effect of Shopping Orientations, Store Trust and Promotion on the Purchase Decision of Generation Z at Gramedia Padang Book Store - Abaharis, Henryanto; Tanzah, Amelia Love (Bina Bangsa International Journal of Business and Management, 2023)
Gramedia is a retail store for books and stationery and various school and office needs that has a comfortable and modern feel. Gramedia bookstore as one of the largest bookstores in Indonesia has a wide selection of products that are attractive to the public. The Gramedia bookstore has succeeded in positioning itself not only as a bookstore, but as a store that provides the most complete stationery and various academic needs in Indonesia. The purpose of this study was to determine the effect of shopping orientations, store trust and promotion on the purchasing decisions of Generation Z at the Gramedia Padang bookstore. The method used in this study using quantitative methods, namely multiple linear regression on shopping orientations, store trust and promotion. The types and sources of data used in this study used primary data which was processed using the SPSS application. From the results of the analysis of shopping orientations obtained a significant value of tcount from ttable, then the hypothesis (H1) in this study was declared rejected. The results of the analysis of the second and third variables obtained a significant value of tcount from ttable, then the hypothesis is declared accepted. Based on the results obtained, it can be concluded that shopping orientations have no and significant effect on purchasing decisions and store trust and promotion variables have a positive and significant effect on purchasing decisions. then the hypothesis (H1) in this study was declared rejected. The results of the analysis of the second and third variables obtained a significant value of tcount from ttable, then the hypothesis is declared accepted. Based on the results obtained, it can be concluded that shopping orientations have no and significant effect on purchasing decisions and store trust and promotion variables have a positive and significant effect on purchasing decisions. then the hypothesis (H1) in this study was declared rejected. The results of the analysis of the second and third variables obtained a significant value of tcount from ttable, then the hypothesis is declared accepted. Based on the results obtained, it can be concluded that shopping orientations have no and significant effect on purchasing decisions and store trust and promotion variables have a positive and significant effect on purchasing decisions